Complementary adoptions and the diffusion of information systems in small and medium enterprises: An exploratory study - Arturo Vega; Barrack Road; Mike Chiasson (International Journal of Business Science & Applied Management (IJBSAM), 2021)
The aim of this study is to explore the diffusion of information systems (IS) in small and medium enterprises (SMEs) as a multifaceted and open social phenomenon, by considering the role and effects of complementary adoptions -in terms of other innovations and their adopters- on the adoption of the IS -focal adoptions. We conceptualised adoption as a staged process (agenda-setting, matching, implementing, restructuring, clarifying, routinising and infusion) and used multiple case studies to guide the fieldwork and analysis. We found that the outcome, timing, and flow of the stages of the focal processes were affected by intricate and multilevel systems of mutually dependent complementary adoptions of innovations and non-innovations by a diversity of adopters, which ultimately determined the results of the focal adoptions. Our constructs define an alternative unit of analysis that provides a comprehensive and realistic view of the possibilities of effectively diffusing IS in SMEs. This emphasises the need to rethink the objects of study, agency functions, theoretical frameworks, and research approaches if we are to understand systems and design and implement system interventions, including public policies.
Keywords: 650; Information systems diffusion; Small and medium enterprises; Multiple adoption dependencies; Unit of analysis; Systems of innovation